Seroprevalencia de la enfermedad de Chagas en pacientes con VIH de un hospital de Nivel III de Iquitos, setiembre 2023 – Marzo 2024 - Quiroz Morey, Alejandro (2024)
Chagas disease (CD) is an endemic disease in 21 countries in the Americascaused by the parasite Trypanosma cruzi. In the Peruvian Amazon, data onthe prevalence of CD are scarce or non-existent, mainly in patients with HIVinfection, although this condition could predispose a more serious and evenfatal condition in HIV patients. There are serological tests that could helpdetermine the seroprevalence in this vulnerable population. The objective ofthe study is to determine the seroprevalence of CD in people with HIV whoattend the Loreto Regional Hospital (HRL). It is a descriptive, prospectivecross-sectional study. The population will be patients with HIV infection whoare treated at the HRL. Sociodemographic, epidemiological and clinical datawill be collected through a semi-structured oral questionnaire. A blood samplewill be obtained by venipuncture for the serological study of T. cruzi. In patientspositive for CD by serological test, PCR will be performed. This study seeks tocontribute to scientific knowledge and understanding of the interactionsbetween infectious diseases, which can help develop more effective strategiesfor the management of patients with co-infections to avoid seriousconsequences on the health of patients with HIV.